2008
DOI: 10.1001/archsurg.143.10.950
|View full text |Cite
|
Sign up to set email alerts
|

Occlusive vs Gauze Dressings for Local Wound Care in Surgical Patients

Abstract: Patients: Two hundred eighty-five hospitalized surgical patients with open wounds. Intervention: Patients received occlusive (ie, foams, alginates, hydrogels, hydrocolloids, hydrofibers, or films) or gauze-based dressings until their wounds were completely healed. Main Outcome Measures: Primary end points were complete wound healing, pain during dressing changes, and costs. Secondary end point was length of hospital stay. Results: Time to complete wound healing did not differ significantly between occlusive (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 26 publications
3
33
2
4
Order By: Relevance
“…5 Healing rates in non-adherent dressing group co-relates with the results of study by Ubbink DT et al 2008. 26 Similar were the findings in study by Dagilatis R et al 25 The present study results of collagen group are correlating with studies by Sundarrajan CR et al showing epithelization in 7-15 days. 23 Whereas Jansson K et al found complete epithelization in 7 days.…”
Section: 22supporting
confidence: 93%
“…5 Healing rates in non-adherent dressing group co-relates with the results of study by Ubbink DT et al 2008. 26 Similar were the findings in study by Dagilatis R et al 25 The present study results of collagen group are correlating with studies by Sundarrajan CR et al showing epithelization in 7-15 days. 23 Whereas Jansson K et al found complete epithelization in 7 days.…”
Section: 22supporting
confidence: 93%
“…11,19 Small or superficial acute wounds may dry uncovered (WG). The dressing choice should depend on the circumstances of the patient and wound (change frequency, leakage, and pain) (WG).…”
Section: What Wound Dressing Materials For Which Wound?mentioning
confidence: 99%
“…Showering the wound area (for < 10 min) is allowed 24 h after surgical wound closure in a hospital, if the patient wishes to do so. 19. If there is a prosthesis beneath the wound, then showering the wound area (for < 10 min) is allowed after 48 h if there are no signs of infection and the treating surgeon agrees.…”
mentioning
confidence: 99%
“…4). The early postoperative inflammatory reaction was caused mainly by neutrophils, lymphocytes, and macrophages migrating to the surgical site [9][10][11][12]. To investigate this phenomenon further, the exact numbers and increased levels of neutrophils, lymphocytes, and monocytes in the blood were measured pre-and postoperatively.…”
Section: Physiological and Immunological Effects Of No Drain Placemenmentioning
confidence: 99%